Estimating the treatment cost of colon cancer at Groote Schuur Hospital - Nnene, Kelechi (Department of Public Health and Family Medicine, 2026)
Background: Due to the high mortality-to-incidence ratio of colon cancer in South Africa, urgent public health measures are needed to improve treatment outcomes. Costing studies can be leveraged to understand the treatment cost burden for colon cancer, providing crucial insights for allocating resources to finance such measures. This study aims to assess treatment options and costs for colon cancer treatment from the perspective of healthcare providers at a public healthcare facility in South Africa. Method: The study used an ingredient-based approach to assess colon cancer treatment costs by stage at the colorectal clinic and combined colorectal oncology unit at Groote Schuur Hospital. The costing process involved two steps: first, treatment options were defined according to facility guidelines and verified through expert interviews; then, these options were linked to relevant cost items for each cancer stage based on expert input. Second, a bottom-up costing method was used to estimate and aggregate per-patient costs across treatment components for each stage. One-way sensitivity analysis addressed uncertainties in post-surgical inpatient admissions and staff categories. All costs are presented in 2024 South African Rands (ZAR) and United States Dollars (USD). Results: Colon cancer treatment components include staging and risk assessment investigations, clinical consultations, surgery and chemotherapy. The estimated guideline-based per-patient costs for treatment are R60,156 ($3,216) for stages I and II (low-risk); R75,132 ($4,017) for high-risk stage II and stage III; and R171,935 ($9,193) for stage IV. Surgical treatment represents a major cost driver, with additional expenses from inpatient admissions following surgery. Sensitivity analysis indicates that reducing postoperative inpatient stay by 25% lowers the treatment cost by approximately 5% across all stages. Conclusion: Colon cancer treatment costs are significant, increasing with each colon cancer stage. To manage these escalating costs and reduce the overall healthcare burden, policies should prioritise early detection and invest in accessible, stage-appropriate interventions to improve patient outcomes.